Features of laboratory tests for diagnosis of rubella in pregnant women - T. D. Grigor’eva; M. A. Belopolskaya; S. S. Vashukova; N. G. Makarova; N. V. Andreeva (Журнал инфектологии, 2014)
Introduction: Despite on mandatory vaccination against rubella, the amount of pregnant women without immunity to rubella may exceed 20%. These women represent a risk group for the rubella disease.Objectives: The goals of the presented work are to analyze the cases of anti-rubella IgM detection in pregnant women, and to develop an algorithm for management of such patients.Materials and Methods: Screening has been performed by ELISA test systems company Radim (Italy). In total 799 patients were examined for rubella in 2013, 56 of them were pregnant women.Results. Positive IgM antibodies to rubella in 2013 have been identified in 5 cases, including 4 pregnant women. A detailed analysis of medical history, clinical and laboratory data has been done. In none of these cases the diagnosis of rubella has been confirmed.Conclusions. The main criterion for the diagnosis of rubella in pregnant women with rubella markers in the absence of clinical symptoms must be a dynamic examination, including study on IgM- and IgG-antibodies to rubella virus. The study must be conducted in the same laboratory at intervals of 10–14 days. In most cases, determination of IgG-antibodies avidity helps to estimate the time of infection. In complicated cases it is recommended to use PCR and immunoblot.